Análise de aspectos físicos e cognitivos da saúde de idosos - Bravalhieri, Anna Alice Vidal (2021)
The substantial increase in the elderly population is a fact that occurs worldwide, aging is considered a sequential, individual, cumulative, irreversible, universal, non-pathological process, of deterioration of a mature organism, unique to all members of a species. The health of the elderly is closely related to the individual's overall functionality, defined as the ability to manage their own life or take care of themselves. A person is considered healthy when they are able to carry out their activities alone, independently and autonomously, even accompanied by comorbidities, the Elderly Living Centers (ELC) are responsible for encouraging active aging, encouraging the elderly's autonomy and independence. Social isolation is an emerging issue in the geriatric population, being a significant threat to health and well-being, representing a worsening in mental health and an increased risk of mortality in the elderly. With the arrival of Covid-19 in Brazil, several measures were taken and distancing is one of the most effective tools for reducing the transmission of the virus. On the other hand, social isolation can have physical, mental and social impacts involving situations of fear, uncertainty and loneliness. This dissertation aimed to assess the physical and cognitive health of the elderly in two moments: firstly in a pre-pandemic living environment and during the pandemic, to assess the impacts of social isolation on physical health and mental health of the elderly in the community. The first study shows that elderly people who perform physical activities in ELC tend to have better motor scores, with lower risk of frailty and vulnerability than elderly people who perform cognitive activities in ELC and sedentary elderly. The second study, on the other hand, shows that healthy elderly people living in the community had mild depressive symptoms and a minimal loneliness rate in times of pandemic. The muscle strength and endurance of the lower limbs was age-appropriate, confirming the independence of the participants in the functional activities of daily living.